CONSCIENTIOUSNESS DAN CAREER ADAPTABILITY PADA MAHASISWA GENERASI Z DI YOGYAKARTA - Aji , Tegar Kartika; Yuniasanti , Reny (Provitae: Jurnal Psikologi Pendidikan, 2025)
Indonesia is expected to experience a demographic bonus between 2030 and 2040. Generation Z, born between 1997 and 2012, will contribute the most to the productive age workforce. This study aims to determine the relationship between the Big Five Personality trait of Conscientiousness and Career Adaptability in Generation Z. this study hypothesizes that there is a positive relationship between Conscientiousness and Career Adaptability in Generation Z, where a higher level of conscientiousness will be followed by a higher level of career adaptability in Generation Z. Conversely, the lower the level of conscientiousness, the lower the career adaptability in Generation Z. The sample for this study consisted of 168 respondents who are active Generation Z students in Yogyakarta aged 18-25 years. This study uses a quantitative correlation method with product-moment correlation data analysis techniques. The measurement tools used are the Career Adaptability Scale (CAAS) and the Conscientiousness Scale. The results show a positive correlation between Conscientiousness and Career Adaptability in Generation Z students (r = 0.559, p < 0.001). The coefficient of determination (R²) is 0.313, indicating that the Conscientiousness variable contributes 31% to Career Adaptability. Based on these results, it is suggested that students need to possess the personality trait of Conscientiousness or diligence to enhance their adaptability to career changes, which will influence their future.